Mentoring Local Tour Guides to Improve English Language Skills in Sade Hamlet, Nusa Tenggara Barat - Endang Sri Wahyuni; Siti Latifah; Ainul Yakin; Satria Rusdy Wijaya; Lalu Ahmad Zaki (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (PKM) in Sade Hamlet, Rembitan Village, NTB, was implemented to mitigate the negative impact of the "Scamming Village" phenomenon that went viral on social media. This issue has tarnished both local and national tourism images, while also undermining the confidence of local tour guides in the destination. The primary goal of this PKM was to enhance English language skills and restore the motivation of local tour guides. Over a period of two years, from 2023 to 2024, 53 local tour guides were mentored using the Before-After method and a flexible mingling technique, allowing training schedules to adapt to participants' work hours. The program was further strengthened by introducing the work motto: "Sade Tourist Local Guide, SMART AND RELIABLE," aimed at fostering confidence and professionalism. The results showed a significant increase in learning motivation, reflected in participants' enthusiasm and attendance during the mentoring sessions, as well as improved English language proficiency in serving tourists. However, challenges such as limited English vocabulary, ineffective communication strategies, inadequate facilities, and time constraints remain. For future PKM activities, it is recommended to focus on enriching vocabulary and enhancing communication strategies, along with providing adequate facilities and more flexible learning schedules, including informal mentoring programs outside of working hours.